2017
DOI: 10.4314/jasem.v20i4.28
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bisphenol A, physicochemical properties and microbial characterization of borehole water stored in plastic containers

Abstract: ABSTRACT:The aim of this study was to evaluate the bisphenol A (BPA), physicochemical properties and microbial characterization of borehole water stored in plastic containers. Three brands of plastic containers filled with borehole water were collected from homes in Ugbowo, Benin city. Physicochemical parameters were determined using standard methods. Total bacterial and coliform counts were determined using the pour plate technique. Conductivity, TDS, Chloride, Sulphate and Nitrate were within the recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Interestingly, 100% and 29% of the samples contained total bacterial and coliform respectively. Similarly, the microbial, heavy metal and estrogenic burden of borehole water in Nigeria are also high and of great concern (Adeghe and Emejulu, 2016;Samuel et al, 2019) post SDG implementation. Samuel et al (2019) reported pathogenic bacteria and coliform (including Salmonella Typhi) from borehole samples from Anambra State.…”
Section: Drinking Water Quality In Nigeria Post-sdg Implementationmentioning
confidence: 99%
“…Interestingly, 100% and 29% of the samples contained total bacterial and coliform respectively. Similarly, the microbial, heavy metal and estrogenic burden of borehole water in Nigeria are also high and of great concern (Adeghe and Emejulu, 2016;Samuel et al, 2019) post SDG implementation. Samuel et al (2019) reported pathogenic bacteria and coliform (including Salmonella Typhi) from borehole samples from Anambra State.…”
Section: Drinking Water Quality In Nigeria Post-sdg Implementationmentioning
confidence: 99%
“…Ingestion, inhalation, or dermal contact have been identified as the major routes of human exposure to BPA (Talpade et al ., 2018). It has been widely reported that increased temperature, elongated storage time, repeated usage, and acidic or basic food or beverages in cans and polycarbonate plastics can facilitate the leaching of the BPA into the contents (vom Saal and Hughes, 2005; Šutiaková, 2012; Adeghe and Emejulu, 2016). The leached BPA ultimately hydrolyze in the food and liquids making the dietary consumption the main source of human exposure (Šutiaková, 2012; Adeghe and Emejulu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that increased temperature, elongated storage time, repeated usage, and acidic or basic food or beverages in cans and polycarbonate plastics can facilitate the leaching of the BPA into the contents (vom Saal and Hughes, 2005; Šutiaková, 2012; Adeghe and Emejulu, 2016). The leached BPA ultimately hydrolyze in the food and liquids making the dietary consumption the main source of human exposure (Šutiaková, 2012; Adeghe and Emejulu, 2016). Similarly, environmental pollution inter alia may lead to exacerbated exposure of BPA (Stragierowicz, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the bacteriological quality of water consumed by members of rural households, it is essential to address the quality of stored drinking water and the conditions under which the water supplies are stored. Storing of water in tanks for days or weeks increases bacteria load and leaching of Bisphenol A and as such reduces the quality of water (Jagals et al, 1999: Adeghe andEmejulu, 2016). According to (Eniola et al, 2007), storage generally reduces the numbers of bacteria which is in contrast to (WHO, 2005) which identified water as a major components for bacteria growth.…”
mentioning
confidence: 99%